Promoting Islamic Value for Green Skill Development in Islamic Vocational High School - Fauziah, R. Siti Pupu; Purnomo, Agustina Multi; Firdaus, Uus; Dani Nanyanto, Asep Bayu; Roestamy, Martin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
Air pollution is a critical issue in Indonesia in 2023, prompting the need to enhance green skills within Vocational High Schools to support a sustainable green economy. The purpose of this study is to investigate the influence of Islamic values on the development of green skills among students. Utilizing quantitative methods, data were collected through online questionnaires distributed to 562 twelfth-grade students at the Islamic Foundation Vocational School in Bogor Regency. The results revealed that Islamic values, particularly beliefs and attitudes towards the environment, significantly impacted the acquisition of green skills. Further analysis identified that Islamic values as a source of inspiration and serenity, along with teachings on tree planting and zero-waste practices, had a partially significant effect. The study concludes that incorporating Islamic religious education into the vocational school curriculum is crucial. These findings offer valuable insights for educators, policymakers, and practitioners, providing a basis for integrating Islamic values into vocational education to enhance green skill development among students.